Mechanical characterisation of a hydrogel-based microfluidic device for tissue culture - Nur Hidayah Jumal. (2013)
Microfluidic devices have been widely used for cell studies. In this project, a hydrogel-based microfluidic device was designed to study the transformation of stem cells into cardiac cells. A Polydimethylsiloxane (PDMS) membrane was sandwiched between two patterned PDMS layers to form the device. The stem cells were to be embedded into collagen and this mixture was to be injected into a central channel in the device. The device was then subjected to vacuum to produce deformations that would induce strain on the stem cells. Concrete rheological data for collagen was sparse and a mechanical characterisation of collagen was done through experimentation. The microfluidic device doubled up as a device for the collagen characterisation and fluorescent microspheres were embedded in the collagen in place of stem cells. The fluorescent microspheres were tracked under a fluorescent microscope, and a graph of the microsphere locations was plotted against time. Data from the graph was used to determine the stiffness of the collagen. Simultaneously, a finite element analysis was done on the microfluidic device to study the feasibility of the design. The results showed that the device design was feasible for low values of collagen stiffness but the device would fail when the stiffness approached the stiffness of PDMS.